Inside Cover: Enhanced Electrokinetics of C−C Bond Splitting during Ethanol Oxidation by using a Pt/Rh/Sn Catalyst with a Partially Oxidized Pt and Rh Core and a SnO2 Shell (ChemCatChem 18/2016). Issue 18 (21st September 2016) - Yang, Guangxing; Frenkel, Anatoly I.; Su, Dong; Teng, Xiaowei
Abstract : The Cover shows a TEM image of PtRhOx‐SnO2 core‐shell particles the authors were lucky to collect during TEM measurements, rather than the usual near‐spherical shape. In their Communication, G. Yang et al. not only show that the image of a perfectly heart‐shaped catalyst particle is eye‐catching, but also an ideal showcase for the combination of art and science, since the highlight of their study is that partially PtRhOx‐SnO2 with an oxidized PtRh core, i.e., the "oxidized Pt‐Rh heart", is an effective catalyst for direct ethanol fuel cell, with a high efficiency of oxidizing ethanol into CO2 . In addition, this cover artwork reflects the great impact of direct ethanol fuel cell research: (i) scale‐up production of bio‐ethanol) can be achieved through fermentation processes using sugar‐and/or cellulose‐containing crops; (ii) growing crops for bioethanol absorbs CO2 emitted into the atmosphere, and therefore is sustainable; (iii) bio‐ethanol can be effectively oxidized into CO2 in fuel cell devices with thermodynamically efficient generation of electricity compared with heat engine. More information can be found in the Communication by G. Yang et al. onpage 2876 in Issue 18, 2016 (DOI:10.1002/cctc.201600429 ).